EFFECT OF CYLINDER HEAD GASKET ADDITION AND VARYING OCTANE NUMBER GASOLINE TO INTERNAL COMBUSTION ENGINE PERFORMANCE - Rahmat, Bahtiar; Wijaya , Mohammad Burhan Rubai; Bahtiar, Fahmy Zuhda; Wirawan, Yuris Bahadur; Muttaqin, Katiko Imamul (Media Mesin: Majalah Teknik Mesin, 2024)
The aim of this research was to investigate the different impacts of compression pressure on power and torque outputs using gasoline RON 92, RON 95, and RON 100. The study involved experiments using a single-cylinder motorcycle engine with a capacity of 125 cm. The selection of this type of engine is based on the popularity of vehicles in Indonesia that use a single-cylinder engine with a capacity of 125 cm. To modify the compression pressure, variations in the number of gaskets were applied to the cylinder head, with quantities of 1 and 3 gaskets. Dynamometer tests were conducted to measure the engine's performance differences. Throughout the testing, the settings for the main jet, pilot jet, and the number of idle screw rotations on the carburetor remain constant. The findings indicate that the engine with the highest compression pressure of 11.8 Kg/cm, using RON 100 gasoline, produces the highest power output at 7.9 kW, with the highest torque at 10 Nm.